Key concepts in creative industries - Potts, Jason; Cunningham, Stuart; Flew, Terry; Keane, Michael; Banks, John (SAGE Key Concepts, 2013)
This book is a clear, comprehensive and accessible tool-kit of ideas, concepts, questions and discussions which will be invaluable to students and practitioners alike. Key Concepts in Creative Industries is set to become the corner stone of an expanding and exciting field of study.